Coupled FEM and experimental analysis to characterize initial crack growth regime in AISI 316L(N) stainless steel. Issue 3 (8th June 2015) - Krishnan, S. A.; Moitra, A.; Sasikala, G.; Albert, S.K.; Bhaduri, A.K.
Abstract : Purpose: – The purpose of this paper is to present a methodology to predict initial crack growth behavior of crack or notch like stress raisers in AISI 316L(N) stainless steel material subjected to monotonic loading condition. Design/methodology/approach: – The methodology for critical crack blunting corresponding to crack initiation in crack or notch like stress raisers is based on critical plastic strain (Epc) at a characteristic distance (lc), where uniform strain (Eu) is considered as Epc and two grain diameter is considered as lc. Further crack growth is based on parabolic crack tip opening displacement (CTOD) scheme established based on coupled experimental and FEM analysis of compact tension (CT) specimen subjected to mode-I loading condition. The FEM predicted load-displacement plots is compared with experimental result of CT specimens with different a / W ratios. It has shown that the proposed methodology could account initial crack blunting appropriately and predict the fracture load and load-displacement plots for initial crack growth regime. Findings: – The results show that for crack growth with near straight crack front, experimental data from a CT specimen of particular a / W ratio coupled with plane strain 2D FEM analysis could predict load vs displacement plots for different a / W ratios when initial crack blunting is accounted appropriately with a local damage model. Originality/value: – The present study is a part of developing methods to analyse fracture behavior of AISI 316L(N) SS material components used for fast breeder reactor-based power plant being built at Kalpakkam, India.